A biallelic variant in POLR2C is associated with congenital hearing loss and male infertility: Case report. (10th January 2023) - Bitarafan, Fatemeh; Razmara, Ehsan; Jafarinia, Ehsan; Almadani, Navid; Garshasbi, Masoud
Abstract: Background: DNA‐directed RNA polymerase II subunit 3 (RPB3) is the third largest subunit of RNA polymerase II and is encoded by the POLR2C (OMIM:180663). A large Iranian family with congenital hearing loss and infertility is described here with genetic and clinical characterizations of five male patients. Methods: After doing clinical examinations, the proband was subjected to karyotyping and GJB2/6 sequencing to rule out the most evident chromosomal and gene abnormalities for male infertility and hearing loss, respectively. A custom‐designed next‐generation sequencing panel was also used to detect mutations in deafness‐related genes. Finally, to reveal the underlying molecular cause(s) justifying hearing loss and male infertility, five male patients and 2 healthy male controls within the family were subjected to paired‐end whole‐exome sequencing (WES). Linkage analysis was also performed based on the data. Results: All male patients showed prelingual sensorineural hearing loss and also decreased sperm motility. Linkage analysis determined 16q21 as the most susceptible locus in which a missense variant in exon 7 of POLR2C —NM_032940.3:c.545T>C;p.(Val182Ala)—was identified as a 'likely pathogenic' variant co‐segregated with phenotypes. Conclusions: Using segregation and in silico analyses, for the first time, we suggested that the NM_032940.3:c.545T>C; p.(Val182Ala) in POLR2C is associated with hearing loss and male infertility.